Survival of patients with peripheral T-cell lymphoma after first relapse or progression: spectrum of disease and rare long-term survivors - Mak, Vivien; Hamm, Jeremey; Chhanabhai, Mukesh; Shenkier, Tamara; Klasa, Richard; Sehn, Laurie H; Villa, Diego; Gascoyne, Randy D; Connors, Joseph M; Savage, Kerry J (Journal of clinical oncology, 2013)
A number of novel therapies are under investigation in relapsed or refractory peripheral T-cell lymphoma (PTCL); however, their relative impact on outcome is unknown. We examined the survival of patients with PTCL after relapse or progression in the absence of hematopoietic stem-cell transplantation and explored factors influencing survival. The three most common subtypes encountered in North America were evaluated: PTCL not otherwise specified (PTCL-NOS), angioimmunoblastic T-cell lymphoma (AITL), and anaplastic large-cell lymphoma (ALCL; anaplastic lymphoma kinase [ALK] positive and ALK negative. After exclusions, 153 patients were analyzed (PTCL-NOS, n = 79 [52%]; AITL, n = 38 [25%]; ALK-positive ALCL, n = 11 [7%]; ALK-negative ALCL, n = 27 [16%; including ALK status unknown, n = 1]). Median time from initial diagnosis to relapse or progression after primary therapy was 6.7 months, and median age at relapse was 66 years (ALK-positive ALCL, 39 years). Median overall survival (OS) and median progression-free survival (PFS) after relapse or progression (second PFS) were 5.5 and 3.1 months, respectively, and were only marginally better in patients who received chemotherapy at relapse (n = 89 [58%]; 6.5 and 3.7 months, respectively). Patients with good performance status (PS) of 0 or 1 (n = 47) at relapse who received chemotherapy had a more favorable OS (P < .001; median OS, 13.7 months) and PFS (P = .006; median second PFS, 5.0 months), which remained significant in multivariate analysis (OS: hazard ratio [HR], 2.09; P = .002; second PFS: HR, 1.66; P = .030). Most patients with relapsed or refractory PTCL have poor outcomes with short survival. Select patients with good PS have more favorable outcomes with standard chemotherapy.